THE DEPICTION OF THE LIVES OF HISORI POETS IN THE WORKS OF NAVOI - Jamahmatov Karomiddin Aynillo oʻgʻli (American Journals Publishing, 2026)
This article discusses the history of the Chaghaniyan literary milieu, its stages of development, and the representatives of this literary environment. In addition, descriptive information about the lives of six poets from Hisor, as presented in Alisher Navoi’s tazkira Majālis un-Nafāʾis, is analyzed.
Keywords: Literary school, Chaghaniyan, Denov, Hisor, Zahiriddin Muhammad Babur, Alisher Navoi, tazkira, image.